2018
DOI: 10.4067/s0718-58392018000100059
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock age and grafting season affect graft success and plant growth of papaya (Carica papaya L.) in greenhouse

Abstract: Papaya (Carica papaya L.) is an important fruit crop in many tropical and subtropical countries; it is commercially propagated through seeds, which lead to production of non true-to-type plants. Grafting for mass multiplication of the selected variety is therefore necessary. The objective of this study was to determine the influence of rootstock age and grafting season on the success of cleft grafting and growth of grafted plants under greenhouse conditions. The trial was conducted using an experimental random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…A 25 day old tomato seedling scion was the best compatible attributes regarding the fruit and tuber yield of pomato. The previous study has proved that a younger scion has a higher regenerating ability likely due to higher meristematic cell activity resulting in faster callus formation and quick healing of the graft union [22]. The highest success of a graft union is associated with intimate contact of the cambial regions both rootstock and scion [23].…”
Section: Discussionmentioning
confidence: 99%
“…A 25 day old tomato seedling scion was the best compatible attributes regarding the fruit and tuber yield of pomato. The previous study has proved that a younger scion has a higher regenerating ability likely due to higher meristematic cell activity resulting in faster callus formation and quick healing of the graft union [22]. The highest success of a graft union is associated with intimate contact of the cambial regions both rootstock and scion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum success percentage i.e., 100% was obtained in mango by following cleft grafting technique in the month of June or March. On the other hand, Allan et al (2010) reported that in papaya side grafting brings about 80% success rate while Nguyen and Yen (2018) recommended cleft grafting using 1-month old rootstocks as the best method for maximum grafting success in papaya. Maximum graft success in plum i.e., 9.67 out of 10 grafts was achieved by following cleft grafting in April suggesting it to be the commercial method for grafting (Mozumder et al, 2017).…”
Section: Grafting Techniques In Fruit Treesmentioning
confidence: 99%
“…This early recovery could also be due to the juvenility of the rootstocks and scions. Indeed, juvenile plants show a high meristematic activity responsible for the healing of the weld between the rootstock and scion [24]. Grafting resumption results physiologically in the fusion of the cambium of the graft and that of the rootstock.…”
Section: Discussionmentioning
confidence: 99%